Defining the challenges and opportunities for using patient‐derived models in prostate cancer research - Brennen, WN; Le Magnen, C; Karkampouna, S; Anselmino, N; Bock, N; Choo, N; Clark, AK; Coleman, IM; Dolgos, R; Ferguson, AM; Goode, DL; Krutihof‐de Julio, M; et al. (Wiley, 2024)
Background: There are relatively few widely used models of prostate cancer compared to other common malignancies. This impedes translational prostate cancer research because the range of models does not reflect the diversity of disease seen in clinical practice. In response to this challenge, research laboratories around the world have been developing new patient‐derived models of prostate cancer, including xenografts, organoids, and tumor explants. Methods: In May 2023, we held a workshop at the Monash University Prato Campus for researchers with expertise in establishing and using a variety of patient‐derived models of prostate cancer. This review summarizes our collective ideas on how patient‐derived models are currently being used, the common challenges, and future opportunities for maximizing their usefulness in prostate cancer research. Results: An increasing number of patient‐derived models for prostate cancer are being developed. Despite their individual limitations and varying success rates, these models are valuable resources for exploring new concepts in prostate cancer biology and for preclinical testing of potential treatments. Here we focus on the need for larger collections of models that represent the changing treatment landscape of prostate cancer, robust readouts for preclinical testing, improved in vitro culture conditions, and integration of the tumor microenvironment. Additional priorities include ensuring model reproducibility, standardization, and replication, and streamlining the exchange of models and data sets among research groups. Conclusions: There are several opportunities to maximize the impact of patient‐derived models on prostate cancer research. We must develop large, diverse and accessible cohorts of models and more sophisticated methods for emulating the intricacy of patient tumors. In this way, we can use the samples that are generously donated by patients to advance the outcomes of patients in the future.